2018
DOI: 10.1093/cid/ciy881
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Next-generation Sequencing Defined Human Immunodeficiency Virus Pretreatment Drug Resistance on Virological Outcomes in the ANRS 12249 Treatment-as-Prevention Trial

Abstract: Background Previous studies in human immunodeficiency virus (HIV)-positive individuals on thymidine analogue backbone antiretroviral therapy (ART) with either nevirapine or efavirenz have suggested poorer virological outcomes in the presence of pretreatment drug resistance (PDR). We assessed the impact of PDR on virological suppression (VS; <50 copies/mL) in individuals prescribed primarily tenofovir/emtricitabine/efavirenz in rural KwaZulu-Natal within a treatment-as-prevention trial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 33 publications
4
56
1
Order By: Relevance
“…Sanger-based HIVDR genotyping reports DRM data as dichotomous (present or absent), whereas NGS-based HIVDR genotyping also reports DRMs as numerical data (relative abundance). This additional information strengthens our ability to assess the clinical impact of a given DRM and to determine and track its overall frequency within a population, which may significantly impact drug regimens and public health approaches to control and reduce HIV transmission 10,14,[49][50][51][52] . Notably, while many NGS HIVDR data analysis pipelines exist 25,[31][32][33][34][35][36][37][38][39] , their design and implementation was conducted independently by different research groups with little coordination among the developers.…”
Section: Discussionmentioning
confidence: 81%
“…Sanger-based HIVDR genotyping reports DRM data as dichotomous (present or absent), whereas NGS-based HIVDR genotyping also reports DRMs as numerical data (relative abundance). This additional information strengthens our ability to assess the clinical impact of a given DRM and to determine and track its overall frequency within a population, which may significantly impact drug regimens and public health approaches to control and reduce HIV transmission 10,14,[49][50][51][52] . Notably, while many NGS HIVDR data analysis pipelines exist 25,[31][32][33][34][35][36][37][38][39] , their design and implementation was conducted independently by different research groups with little coordination among the developers.…”
Section: Discussionmentioning
confidence: 81%
“…[12][13][14] By contrast, the ANRS 12249 Treatment as Prevention Trial 15 reported that the most common NNRTI mutation, K103N, when detected alone, was not associated with increased risk of VF on an NNRTI-based single tablet regimen containing tenofovir, emtricitabine and efavirenz. 16 A study in Kenya similarly suggested isolated K103N might have limited impact on EFV-based ART. 17 These con icting data have generated controversy in the eld on optimal rst-line regimens to balance safety, tolerability, cost, and the impact of circulating NNRTI drug resistance on virologic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Derache and colleagues is the largest to assess the effect of baseline NNRTI resistance on the virological response to the fixed-dose combination of TDF/emtricitabine (FTC)/efavirenz (EFV), one of the WHO-recommended first-line ART regimens [3]. It is also one of the largest studies to quantify PDR prevalence using a next-generation sequencing technology, Illumina MiSeq, in place of the more common dideoxynucleoside Sanger sequencing technology.…”
mentioning
confidence: 99%